Analysis of hierarchical identity based encryption schemes and its applicability to computing environments. (October 2017) - Daniel, Renu Mary; Rajsingh, Elijah Blessing; Silas, Salaja
Abstract: Hierarchical Identity Based Encryption (HIBE) enhances the scalability of Identity based encryption scheme, by sharing the workload of the root Private Key Generator (PKG) among multiple lower-level PKGs, facilitating intermediate key escrows and private key delegation. Owing to its structure, HIBE can be deployed to provide access control in cloud, pervasive computing systems, wireless sensor networks and Massively Multiplayer Online Role-Playing Games (MMORPGs). Additionally, HIBE can be used to perform search on encrypted data, forward secure encryption, fully private communication, limited delegation and damage control. This paper evaluates different approaches in the construction of HIBE protocols to determine practical frameworks. Specific criterions like cryptographic proof models, tightness of the reduction, recipient anonymity, hardness assumptions, bounded depth, revocability, types of pairing and ciphertext indistinguishability properties, were used as benchmarks for assessing each scheme. The efficiency in terms of storage and computation overhead, was estimated to identify suitable protocols for securing different computing environments. The future prospective applications of HIBE protocols were also investigated.